A method and sensor for detecting L-glutamic acid based on polymer film modified electrode
By electropolymerizing polytryptophan and acidified carbon nanotubes on a glassy carbon electrode to form a PTrp/MWCNTs/GCE electrode, the existing L-glutamic acid sensor requires enzymes and complex preparation problems, and achieves high sensitivity and low cost. Cost of L-Glutamic Acid Assay.
Patent Information
- Application Number
- CN201910532505.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2019-06-19
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2039-06-19
AI Technical Summary
Existing L-glutamate electrochemical sensors require the use of enzymes, which leads to high costs and limited use conditions. The preparation process of the second-generation sensors is complex and has low sensitivity.
A polytryptophan (PTrp) film was deposited on acidified multi-walled carbon nanotubes (MWCNTs) modified glassy carbon electrode (GCE) using an electropolymerization method to form a PTrp/MWCNTs/GCE polymeric film modified electrode for L-valley Detection of amino acids.
Highly sensitive detection of L-glutamic acid is achieved, with a detection limit of 2.580×10-8mol/L. It has good selectivity, reproducibility and stability, and is suitable for the detection of pig serum samples.
Smart Images

Figure CN110220959B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of chemical / biological sensing, and in particular relates to an L-glutamic acid detection method and a sensor based on a polymer film modified electrode. Background Art
[0002] L-Glutamic acid (L-Glu) is one of the 20 common amino acids in organisms. As a flavor additive, it is widely present in food and plays a very important role in life health, clinical medicine, food processing and other fields. L-Glutamic acid is an important excitatory neurotransmitter in mammals and is related to certain behavioral patterns such as learning and memory. Changes in the concentration of L-glutamate in a specific area of the brain are closely related to diseases such as Alzheimer's disease and Parkinson's disease. Moreover, due to the lack of L-glutamate in foods such as vegetables, L-glutamate is usually added to diets, foods and drug formulations. However, excessive consumption of L-glutamate can cause adverse reactions such as headaches and stomachaches. In addition, as a chemical raw material, L-glutamate is used to produce important biological reagents such as 3-cyanopropionate and succinonitrile. Therefore, it is necessary to establish a simple, accurate, fast and inexpensive method for determining the content of L-glutamate in food processing, drugs, biological fluids and clinical analysis.
[0003] Conventional different analytical methods have been applied to the detection of L-glutamic acid, such as high performance liquid chromatography, capillary electrophoresis, fluorescence detection, and chemiluminescence. Compared with these methods, the electrochemical method has the advantages of high accuracy and sensitivity, simple operation, and strong repeatability, and is therefore widely used in the detection of nitrogen-containing small molecules such as L-glutamic acid.
[0004] According to the electron transfer mode, L-glutamate electrochemical sensors can be divided into two generations. The first generation of sensors is the most widely used, and detection is achieved by measuring the consumed O2 or produced H2O2. The second generation of sensors uses redox mediators to transfer the electrons generated in the electrochemical reaction to the surface of the electrode for detection. Compared with the two generations of L-glutamate sensors, although the second generation of sensors has a complex preparation process and low sensitivity, it has a lower detection potential and better selectivity. However, both the first and second generation sensors involve the use of enzymes, which increases the cost of the sensor and limits the conditions for the use of the sensor. Therefore, many researchers focus on the development of a new generation of enzyme-free sensors using cheap materials. Jamal et al. used the excellent electrocatalytic ability of Ni to prepare Ni nanowire electrodes to achieve enzyme-free detection of L-glutamate with a detection limit of 68.0 μmol / L.
[0005] In addition to nanomaterials, conductive polymers are widely used in the field of electrocatalysis due to their good stability, selectivity and reproducibility. Tryptophan is one of the 20 common amino acids and can be easily fixed on the electrode surface by electropolymerization to form polytryptophan. Polytryptophan forms a superposition of multiple tryptophans and an extension of free carboxyl groups through the combination of amino and carboxyl groups, and exhibits excellent performance in electrochemical applications. Carbon nanotubes are also a class of materials with wide applications. They have a large surface area, good conductivity and strong stability, which can promote electron transfer between reactants and electrodes and improve the sensitivity of electrodes. However, to date, there has been no report on L-glutamate enzyme-free modified electrodes based on polytryptophan (PTrp) loaded carbon nanotubes. Summary of the invention
[0006] The present invention aims to overcome the deficiencies of the prior art and provide a method and a sensor for detecting L-glutamic acid based on a polymer film modified electrode.
[0007] In order to achieve the above object, the technical solution provided by the present invention is:
[0008] The L-glutamic acid detection method based on the polymer film modified electrode comprises the following steps:
[0009] (1) Preparing acidified MWCNTs: placing MWCNTs in a mixed acid of concentrated sulfuric acid and concentrated nitric acid, and then stirring and reflux heating in an oil bath at 120-180° C. for 10-60 min. After the mixed solution is cooled, centrifuging at a speed of 10,000-15,000 rpm for 3-30 min, discarding the supernatant, and the precipitate is the acidified MWCNTs, which is washed and dried, and then ground and pulverized for later use; wherein the volume ratio of concentrated sulfuric acid to concentrated nitric acid in the mixed acid is (1-5):1, and the ratio of MWCNTs to the mixed acid is (150-250) g: (35-45) mL;
[0010] (2) Preparation of PTrp / MWCNTs / GCE polymer film modified electrode: polish the surface of the glassy carbon electrode, clean it with ultrasound and then air dry it; place the acidified MWCNTs in an anhydrous ethanol solution and ultrasonically disperse them to obtain a MWCNTs dispersion with a MWCNTs concentration of 0.5 to 2.0 mg / mL; drop the MWCNTs dispersion on the surface of the glassy carbon electrode and dry it to obtain MWCNTs / GCE; then place the MWCNTs / GCE polymer film modified electrode in a phosphate buffer solution containing 0.03 to 0.09 mol / L L-Trp, and scan 20 to 25 cycles in the range of -0.2 to 2.0 V using cyclic voltammetry to obtain a PTrp / MWCNTs / GCE polymer film modified electrode;
[0011] (3) A three-electrode system was formed using a PTrp / MWCNTs / GCE polymer film modified electrode as the working electrode, a silver / silver chloride electrode as the reference electrode, and a platinum wire electrode as the counter electrode. Cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) were then used to investigate the electrochemical behavior of L-glutamate on different modified electrodes. Differential pulse voltammetry (DPV) was used to test L-glutamate at different concentrations, and a working standard curve was drawn. The standard addition method was then used to detect L-glutamate in the sample.
[0012] Preferably, in step (2), the surface of the glassy carbon electrode is polished using 0.3 μm and 0.05 μm alumina powders, respectively.
[0013] Preferably, the diameter of the glassy carbon electrode in step (2) is 3 mm, 3.0 to 7.0 μL, preferably 5 μL, of the MWCNTs dispersion is dropwise applied to the surface of the glassy carbon electrode, and MWCNTs / GCE is obtained after drying. The MWCNTs / GCE electrode is placed in 10.0 mL of a phosphate buffer solution containing 0.03 to 0.09 mol / L L-Trp; the phosphate buffer solution (PBS, pH 7.0, 0.01 to 0.10 mol / L) is preferably a phosphate buffer solution (PBS, pH 7.0, 0.02 mol / L).
[0014] Preferably, in step (3), the concentration of Fe(CN) in the mixture is 2.0 mmol / L. 4- / 3- -0.20mol / L Na2SO4 solution using cyclic voltammetry and electrochemical impedance spectroscopy to investigate the electrochemical behavior of L-glutamic acid on different modified electrodes; in acetic acid-sodium acetate buffer solution (SAB) using differential pulse voltammetry to test different concentrations of L-glutamic acid, plot a working standard curve, and then use the standard addition method to detect L-glutamic acid in the sample to be tested. The concentration of the acetic acid-sodium acetate buffer solution is 0.01-0.20mol / L, preferably 0.10mol / L; the pH of the acetic acid-sodium acetate buffer solution is pH3.60-4.20, preferably pH3.90.
[0015] The L-glutamate detection sensor based on a polymer film modified electrode comprises a polymer film modified electrode as a working electrode; the polymer film modified electrode comprises a glassy carbon matrix (5), the surface of the glassy carbon matrix (5) is modified with an acidified MWCNTs layer (6), the acidified MWCNTs layer (6) is loaded with a PTrp film layer (7), and the PTrp film layer (7) contains an L-Trp unit (9).
[0016] Preferably, the sensor comprises a glassy carbon matrix (5) having a thickness of 1.0 to 5.0 mm, an acidified MWCNTs layer (6) having a thickness of 20 to 200 nm, and a PTrp film layer (7) having a thickness of 5 to 50 nm.
[0017] Preferably, the sensor has a good linear relationship with the concentration of L-glutamic acid, and the linear range of detection is 5.000×10 -8 ~1.500×10 -5 mol / L, the detection limit is 2.580×10 -8 mol / L.
[0018] The present invention uses an electropolymerization method to deposit a polytryptophan (PTrp) film on an acidified multi-walled carbon nanotube (MWCNTs) modified glassy carbon electrode (GCE) to form a polytryptophan-loaded carbon nanotube modified glassy carbon electrode (PTrp / MWCNTs / GCE) that can be used for sensitive detection of L-glutamic acid (L-Glu). The material morphology is characterized by transmission electron microscopy (TEM), and the electrochemical behavior and reaction mechanism of L-Glu molecules on different modified electrodes are investigated by cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). It is found that PTrp / MWCNTs / GCE exhibits good electrocatalytic oxidation properties for L-Glu. In acetic acid-sodium acetate buffer solution (SAB), the differential pulse voltammetry (DPV) response peak current of the modified electrode is significantly correlated with the concentration of L-Glu at 5.000×10 -8 ~1.500×10 -5 mol / L range, with a good linear relationship and a detection limit of 2.580×10 -8 mol / L (S / N=3). The electrode has high selectivity, good reproducibility and stability. The electrode was used to determine L-Glu in pig serum samples, and the results were consistent with those of the HPLC method, and the recovery rate reached 94.8% to 104.5%, indicating that the electrode is expected to become a new means of non-enzymatic detection of glutamate and can be applied to the fields of life analysis and animal nutrition. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 Schematic diagram of the working structure of the L-glutamate detection sensor based on polymer film modified electrode;
[0020] Figure 2 Schematic diagram of the preparation of polymer membrane electrode PTrp / MWCNTs / GCE;
[0021] Figure 3 Transmission electron microscopy characterization images of different modified materials such as MWCNTs (A) and PTrp / MWCNTs (B);
[0022] Figure 4 : GCE(a), MWCNTs / GCE(b), PTrp / MWCNTs / GCE(c) at 2.0mmol / L[Fe(CN)] 3- / 4- -Cyclic voltammogram (A) and electrochemical impedance spectroscopy (EIS) diagram in 0.20 mol / L Na2SO4 solution;
[0023] Figure 5 : GCE(a), MWCNTs / GCE(b), PTrp / GCE(c), PTrp / MWCNTs / GCE(d) containing 1.000×10 -5 Cyclic voltammogram of mol / L L-Glu in 0.10 mol / L acetic acid-sodium acetate (pH=3.90) solution;
[0024] Figure 6 The effects of different experimental parameters on the DPV response current I: carbon nanotube dosage (A), tryptophan concentration (B), and polymerization number (C);
[0025] Figure 7 The graphs are the relationship between the oxidation peak current (A) and peak potential (B) of L-Glu and pH at different pH values;
[0026] Figure 8 CV response curves of PTrp / MWCNTs / GCE to L-Glu at different scan rates (A), the relationship curve between oxidation peak current and scan rate (B), and the relationship curve between oxidation peak potential and the natural logarithm of scan rate (C);
[0027] Fig. 9 The oxidation mechanism diagram of L-Glu on PTrp / MWCNTs / GCE electrode;
[0028] Fig.10 DPV response curve of PTrp / MWCNTs / GCE to different concentrations of L-Glu (A) and the linear relationship curve between peak current and concentration (B);
[0029] Fig.11 This is a diagram showing the effect of interfering substances on the PTrp / MWCNTs / GCE electrode.
[0030] Figure 1 In the figure: 1. silver / silver chloride electrode; 2. platinum wire electrode; 3. glassy carbon electrode; 4. test solution; 5. glassy carbon matrix; 6. acidified MWCNTs layer; 7. PTrp film layer; 8. L-Glu; 9. L-Trp unit. DETAILED DESCRIPTION
[0031] All reagents used in the examples were of analytical grade (AR), and the experimental water was ultrapure water (resistivity ≥ 18.3 MΩ·cm). In the following description, the description of amino acids uses English abbreviations.
[0032] 1. Experimental process
[0033] 1. Preparation of MWCNTs
[0034] 200 g of MWCNTs were placed in a mixed acid (40 mL) of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1, and then stirred and refluxed in an oil bath at 150°C for 15 minutes. After the mixture was cooled, it was centrifuged at 12000 rpm for 5 minutes, and the supernatant was discarded. The lower precipitate was the acidified MWCNTs. The product was washed three times with ultrapure water to remove excess acid, and then dried in a vacuum drying oven at 75°C overnight. Finally, the product was ground and pulverized for use.
[0035] 2. Preparation of PTrp / MWCNTs / GCE polymer film modified electrode
[0036] The surface of the glassy carbon electrode (GCE, 3 mm in diameter) was polished into a mirror surface using 0.3 and 0.05 μm alumina powder, respectively, and then ultrasonically washed with anhydrous ethanol and ultrapure water for 5 min in sequence, and then dried for use.
[0037] Take 5.0 mg of acidified MWCNTs and place them in 5.0 mL of anhydrous ethanol solution and ultrasonically vibrate for 30 minutes to obtain a black MWCNTs dispersion (1.0 mg / mL). Measure 5.0 μL of the MWCNTs dispersion and apply it on the surface of the glassy carbon electrode. After drying, MWCNTs / GCE is obtained. The MWCNTs / GCE electrode is placed in 10.0 mL of phosphate buffer solution (PBS, pH 7.0, 0.02 mol / L) containing 0.06 mol / L L-Trp, and the cyclic voltammetry method is used to scan 22 circles in the range of -0.2 to 2.0 V to obtain the PTrp / MWCNTs / GCE electrode. The preparation process is as follows Figure 2 shown.
[0038] 3. L-Glu electrochemical detection
[0039] See also Figure 1 The prepared glassy carbon electrode 3 was used as the working electrode, the silver / silver chloride electrode 1 was used as the reference electrode, and the platinum wire electrode 2 was used as the auxiliary electrode to construct a three-electrode system for measurement. 4- / 3--0.20mol / L Na2SO4 solution was used to test the electrochemical behavior by cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS); the DPV test of L-Glu 8 was carried out in 0.10mol / LCH3COOH-CH3COONa (pH=3.90) buffer solution, and the response curve and linear relationship of the L-Glu concentration gradient (0.050, 0.100, 0.300, 0.500, 0.800, 1.000, 3.000, 5.000, 8.000, 10.00, 15.00μM) were detected.
[0040] The surface-modified glassy carbon electrode 3 is the polymer-modified electrode in the L-glutamate detection sensor based on the polymer-modified electrode according to the present invention; the polymer-modified electrode comprises a glassy carbon matrix 5, the surface of the glassy carbon matrix 5 is modified with an acidified MWCNTs layer 6, the acidified MWCNTs layer 6 is loaded with a PTrp film layer 7, and the PTrp film layer 7 contains L-Trp units 9. The thickness of the glassy carbon matrix 5 of the sensor is 1.0 to 5.0 mm, the thickness of the acidified MWCNTs layer 6 is 20 to 200 nm, and the thickness of the PTrp film layer 7 is 5 to 50 nm.
[0041] 4. Sample processing and determination
[0042] The pig blood samples were from three-way hybrid piglets (weight 10-15 kg) bred by the Institute of Subtropical Agriculture Ecology, Chinese Academy of Sciences (Changsha). 5.0 mL of pig blood was taken from each pig, centrifuged at 4500 r / min for 15 min, and the supernatant was placed in a 5 mL glass centrifuge tube. This was repeated three times, and the supernatant was placed in a glass tube and stored at 4 ° C for later use. The standard addition method was used to detect L-Glu in the pig serum sample (test solution 4). Six different pig serum samples (10.00 μL) were added to the acetic acid-sodium acetate buffer solution (9.990 mL) with a pH of 3.90, and then different concentrations of L-Glu (0.200, 0.400, 0.600, 0.800, 1.000, 1.200 μM) were added to the pig serum sample solution, and the DPV method was used for determination.
[0043] 2. Experimental Results and Analysis
[0044] 1. Characterization of materials
[0045] 1.1 Morphology Characterization
[0046] The morphologies of acidified MWCNTs and PTrp / MWCNTs / GCE were characterized by TEM. Figure 3As shown. Unmodified MWCNTs are a type of lyophobic tube material. There are strong van der Waals forces between MWCNTs, so MWCNTs are highly entangled ( Figure 3 A). Figure 3 B shows that a tight film is attached to the surface of MWCNTs, indicating that tryptophan has been successfully polymerized to the electrode surface. Figure 3 The increase in A is because the electropolymerized tryptophan is negatively charged, and when it is attached to the surface of carbon nanotubes, the electrostatic repulsion makes the MWCNTs more dispersed.
[0047] 1.2 Electrochemical characterization
[0048] The electrochemical characterization of the modified electrode preparation process was carried out using cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). Figure 4 (A) and (B) are bare electrodes and electrodes modified with different materials in 2.0 mM [Fe(CN)] 3- / 4- -CV and EIS diagrams in 0.20M Na2SO4 solution.
[0049] Figure 4 In (A), GCE (curve a) shows an oxidation peak and a reduction peak at 0.129 V and 0.194 V, respectively. The redox peak currents of the MWCNTs / GCE electrode (curve b) modified with MWCNTs increase simultaneously, corresponding to Figure 4 The resistance value of curve b in (B) decreases because the network structure of acidified MWCNTs increases the surface area of the electrode and increases the sensitivity, indicating that MWCNTs are successfully modified on the electrode surface. The redox current of the PTrp / MWCNTs / GCE electrode (curve c) after electropolymerization of tryptophan is further increased, corresponding to Figure 4 The resistance value of curve c in (B) decreases because a layer of charged film is polymerized on the electrode surface. At the same time, the electrostatic repulsion makes the MWCNTs more dispersed, which increases the surface of the electrode and greatly promotes the transfer of electrons. This is consistent with the TEM characterization results, indicating that the PTrp / MWCNTs / GCE electrode was successfully prepared.
[0050] 2. Electrochemical behavior of L-Glu
[0051] Cyclic voltammetry (CV) was used to study the effects of different electrodes on the -5 Electrochemical behavior of acetic acid-sodium acetate solution (pH=3.90) containing 1 mol / L L-Glu. Figure 5As shown, there is no oxidation peak of L-Glu on the GCE (curve a) and MWCNTs / GCE (curve b) electrodes, indicating that GCE and MWCNTs / GCE have no response to L-Glu. However, PTrp / GCE (curve c) produces an oxidation peak at 0.235V, indicating that polymerized tryptophan has a good oxidation effect on L-Glu. Compared with PTrp / GCE, the oxidation peak potential of PTrp / MWCNTs / GCE for L-Glu shifted positively to 0.272V, and the response current expanded by 1.6 times, indicating that the composite of MWCNTs and PTrp enhances the conductivity and electrocatalytic oxidation, thereby promoting the electrocatalytic oxidation reaction of L-Glu on the electrode surface.
[0052] 3. Condition optimization
[0053] 3.1. Optimization of MWCNTs dosage
[0054] In order to explore the optimal amount of acidified multi-walled carbon nanotubes (MWCNTs) dispersion (optimized concentration 1.0 mg / mL), the modified electrode with different amounts of acidified MWCNTs was used to detect 1.000×10 -5 mol / L L-Glu, the response peak current and the amount of acidified MWCNTs dispersion are shown in Figure 6 A. As shown in the figure, the response peak current increases with the increase of the volume of the acidified MWCNTs dispersion. This is because the unique structure of the acidified MWCNTs increases the surface area of the electrode and improves the electron transfer rate. However, when the amount of acidified MWCNTs exceeds 5.0μL, the response peak current decreases because when the acidified MWCNTs are dripped in excess, a thicker film will be formed, which hinders the transfer of electrons on the electrode surface. Therefore, the optimal amount of acidified MWCNTs dispersion (1.0mg / mL) is 5.0μL.
[0055] 3.2. L-Trp concentration optimization
[0056] The concentration of L-Trp is an important factor affecting the peak current of glutamate response, so it is necessary to optimize the concentration of L-Trp. The modified electrodes prepared by polymerization at different L-Trp concentrations were used to detect 1.000×10 -5 mol / L L-Glu, the results are as follows Figure 6 As shown in Figure B, with the increase of L-Trp concentration, the response peak current of L-Glu continued to increase until the L-Trp concentration reached 0.06 mol / L. This is because the electropolymerized L-Trp film has a certain catalytic activity for L-Glu. However, when the L-Trp concentration exceeds 0.06 mol / L, the peak current continues to decrease. This is because the PTrp film is too thick and reduces the conductivity of the electrode. Therefore, the optimal tryptophan concentration during electropolymerization is 0.06 mol / L.
[0057] 3.3、Optimization of the number of aggregation circles
[0058] The number of polymerization circles affects the structure of PTrp and is also an important factor affecting the peak current of L-Glu response. Figure 6 C is the modified electrode prepared under different scanning numbers to detect 1.000×10 -5 The response peak current curve of mol / L L-Glu shows that the peak current increases with the increasing number of scanning circles. This is because the more scanning circles, the thicker the electrode surface film, which is more conducive to the electrocatalysis of L-Glu. However, when the scanning circle number is greater than 22, the peak current begins to decrease slowly. This is because when the surface film is too thick, mass transfer resistance will be generated, which is not conducive to the recognition of L-Glu. Therefore, the optimal number of polymerization circles is 22.
[0059] 3.4 Effect of pH on the electrochemical behavior of L-Glu
[0060] The DPV method was used to investigate the relationship between the oxidation peak current and peak potential of L-Glu at the modified electrode PTrp / MWCNTs / GCE and pH when the buffer solution (0.10 mol / L CH3COOH-CH3COONa) pH was 3.0-5.0. The results are shown in Figure 7 As shown. Figure 7 A It can be seen that when the pH is 3.0-3.9, the oxidation peak current of L-Glu gradually increases with the increase of pH value; when the pH exceeds 3.9, the L-Glu peak current gradually decreases with the increase of pH. This is because the pH of the solution will affect the charge properties of L-Glu and PTrp / MWCNTs composite membrane, and then affect the electron transfer and proton transfer between the solution and the electrode. When the pH is too low, the membrane will dissolve, which is not conducive to the transfer of electrons; when the pH is too high, because L-Glu is an acidic amino acid, it will be electronegative, and electrostatic repulsion will occur between the electrode, which is also not conducive to the transfer of electrons. Only when pH = 3.9 (i.e., C H+ =10 -3.9 ), the electron transfer efficiency reaches the highest and the oxidation peak current also reaches the maximum, so acetic acid-sodium acetate buffer solution (SAB) with pH = 3.9 is selected as the best base solution for detecting L-Glu.
[0061] Depend on Figure 7 B shows that there is a linear relationship between the peak potential of L-Glu and the pH value of the solution, and the linear equation is E pa =–0.0547pH+0.4021(R 2 =0.9947), indicating that there is a process of electron and proton transfer in the reaction of L-Glu on the electrode surface; according to the Nernst equation: E p=0.05916(m / n)pH+E0, where m is the number of protons transferred in the reaction and n is the number of electrons transferred. It can be concluded that m=0.925n, that is, m≈n, indicating that the number of electrons and protons transferred during the reaction of L-Glu on the modified electrode interface is equal.
[0062] 4. Discussion on the oxidation mechanism of L-Glu on modified electrode
[0063] The CV method was used to study the relationship between the peak current and peak potential of L-Glu and the change of scanning rate. The results are as follows: Figure 8 As shown. Figure 8 It can be seen that when the scan rate increases from 20mV / s to 160mV / s, the oxidation peak current of L-Glu increases accordingly, and it can be seen that the reaction of L-Glu on the electrode is an irreversible oxidation process. Figure 8 B shows that the oxidation peak current of L-Glu is linearly related to the scan rate, and the linear equation is I p =–12.19v–0.8485(R 2 =0.9962), which indicates that the reaction of L-Glu on the modified electrode is an adsorption-controlled process. Figure 8 C shows that the oxidation peak potential of L-Glu is linearly related to the natural logarithm of the scan rate, and the linear equation is E pa =0.019lnv+0.319(R 2 =0.9961). According to the Laviron formula:
[0064]
[0065] Among them, E p is the oxidation peak potential, E 0 ' is the formula potential, α is the electron transfer coefficient, n is the number of electrons transferred, T is the temperature, R is the molar gas constant, F is the Faraday constant, k 0 is the standard heterogeneous electron transfer rate constant, D is the diffusion coefficient, and v is the scan rate. By comparing the above formula, we can get α·n=0.6760. Since 0.3<α<0.6 in the irreversible electrode reaction at room temperature, it can be concluded that when α=0.338, n=2, that is, the number of electron transfers in the L-Glu oxidation process is 2. From the above, we can get the number of proton transfers m=2. It is thus deduced that the reaction process of L-Glu on the electrode surface is as follows Fig. 9 shown.
[0066] 5. Linear range and detection limit
[0067] Under the optimal conditions, different concentrations of L-Glu were detected in acetic acid-sodium acetate buffer (0.10 mol / L, pH = 3.90) using the PTrp / MWCNTs / GCE electrode by DPV method. Fig.10 shown. Fig.10 A is the differential pulse voltammetry curve of PTrp / MWCNTs / GCE electrode to different concentrations of L-Glu. It can be seen from the figure that the DPV response peak current increases with the increase of L-Glu concentration. Fig.10 (B) It can be seen that the peak current of the response is related to the L-Glu concentration at 5.000×10 -8 ~1.500×10 -5 mol / L shows a good linear relationship, and the linear equation is I p =–0.2853C–3.1760(R 2 =0.9956), the detection limit is 2.580×10 -8 mol / L (S / N=3). Comparing the electrode prepared by the present invention with other methods in the literature (see Table 1), it can be seen that the electrode prepared by the present invention has more excellent performance, especially compared with the enzyme-free electrode.
[0068] Table 1 Comparison of detection performance of different electrodes
[0069] Table 1 Comparison of performance with different modified electrodes
[0070]
[0071] Note:GluOx:Glutamate Oxide;PtNP:Pt nanoparticles;AuNA:Au nanowire array;NiNAE:Ni nano array;MIP:molecular imprinted polymer;GCE:glass carbonelectrode;Gldh:Glutamated ehydrogenase;SWNTS:single walled carbon nanotubes;PVA:photo-crosslinkable polymer;SPE:screen printed electrode; PTrp: Polytryptophan; MWCNTs: multi-walled carbon nanotubes.
[0072] The relevant references mentioned in Table 1 are as follows:
[0073] [6]Jamal M.,Xu J.,Razeeb KM,Biosens.Bioelectron.,2010,26(4),1420-1424.
[0074] [7] Chang KS, Chang CK, Chou SF, Biosens. Bioelectron., 2007, 22(12), 2914-2920.
[0075]
[27] Jamal M.,Hasan M.,Mathewson A.,Biosens.Bioelectron.,2012,40(1):213-218.
[0076]
[29] Zhao Shuo, Cui Lifeng, Shen Qing. Environmental Science and Technology, 2012, 35(11), 70-74.
[0077]
[37] Jamal M., Worsfold O., Mccormac T., Biosens. Bioelectron., 2009, 24(9), 2926-2930.
[0078]
[38] Meng L., Wu P., Chen G., Biosens. Bioelectron., 2009, 24(6), 1751-1756.
[0079]
[39] Gholizadeh A.,Shahrokhian S.,Zad AI,Biosens.Bioelectron.,2012,31,110-115.
[0080]
[40] Chang K.,Hsu W.,Chen H.,Anal.Chim.Acta,2003,481(2),199-208.
[0081] 6. Reproducibility, repeatability and stability of electrodes
[0082] Five modified electrodes prepared under the same conditions from the same batch were used to detect 1.000×10 -5 mol / L L-Glu, the relative standard deviation was 4.7%, indicating that the electrode preparation method has good reproducibility. -5 and 1.000×10 -6mol / L L-Glu was tested 8 times in a row, and the relative standard deviations were 2.3% and 3.4%, respectively, indicating that the electrode prepared by this method has good repeatability. In addition, in order to explore the stability of the electrode, the prepared electrode was stored at room temperature and the DPV method was used every day to measure the concentration of 1.000×10 -5 After 30 days of continuous measurement of 1 mol / L L-Glu, the response current of the electrode decreased by 13.24% compared with the initial value, indicating that the electrode has good stability and long service life.
[0083] 7. Anti-interference test
[0084] The DPV method was used to investigate the interference of some common amino acids on the determination of L-Glu. The interference substances with a concentration of 50 times (5.000×10 -4 mol / L) alone and with L-Glu (1.000×10 -5 mol / L) when mixed, the response peak current is as follows Fig.11 As shown. Fig.11 It can be seen that L-aspartic acid (L-Asp), L-tryptophan (L-Trp), L-tyrosine (L-Tyr), L-lysine (L-Lys), L-arginine (L-Arg), L-histidine (L-His), L-glycine (L-Gly), L-cysteine (L-Cys), and L-threonine (L-Thr) will not interfere with the detection of L-Glu, indicating that the electrode has good selectivity.
[0085] 8. Actual sample testing
[0086] Take the pretreated porcine serum sample, compare the prepared polymer membrane electrode PTrp / MWCNTs / GCE with the results measured by high performance liquid chromatography, and the results are shown in Table 2. It can be seen from Table 2 that the results measured by this method are basically consistent with those measured by high performance liquid chromatography, and the relative error is about 5.0%, indicating that this method has good accuracy. The porcine serum sample was measured by the spike recovery method, 10.0 μL of the porcine serum sample was taken in 9.990 mL of acetic acid-sodium acetate buffer solution (pH 3.90), and then different concentrations of standard L-Glu were added for detection and the recovery rate was calculated. The results are shown in Table 3, and the recovery rate is 94.8% to 104.5%, indicating that the electrode can be used for the detection of actual samples.
[0087] Table 2 Comparison of different methods for the detection of L-Glu in pig serum samples
[0088] Table2 Comparison of different methods for detection of L-Glu inpiglet serum samples (n=6)
[0089]
[0090] Table 3 Application of PTrp / MWCNTs / GCE in the detection of L-Glu in pig serum samples
[0091] Table3 Application of PTrp / MWCNTs / GCE to determination of L-glu inpiglet serum samples (n=6)
[0092]
[0093] The present invention adopts an electropolymerization method to prepare an L-glutamate detection sensor based on a polymer film modified electrode (PTrp / MWCNTs / GCE). The sensor has electrocatalytic oxidation activity for L-Glu and has a good linear response relationship. The detection limit is 2.580×10 -8 mol / L. At the same time, the sensor has good selectivity, strong repeatability and high stability. The test results are consistent with HPLC. It can be applied to the detection of L-Glu in pig serum samples. It is expected to develop into a new means of non-enzymatic detection of L-glutamate, which can be applied to life analysis and animal breeding.
Claims
1. A method for detecting L-glutamic acid based on a polymer film modified electrode, characterized in that: The method comprises the following steps: (1) Preparation of acidified MWCNTs: MWCNTs are placed in a mixed acid of concentrated sulfuric acid and concentrated nitric acid, and then stirred and refluxed in an oil bath at 120-180°C for 10-60 min. After the mixed solution is cooled, it is centrifuged at a speed of 10,000-15,000 rpm for 3-30 min, and the supernatant is discarded. The precipitate is the acidified MWCNTs, which is washed and dried, and then ground and crushed for later use; wherein the volume ratio of concentrated sulfuric acid to concentrated nitric acid in the mixed acid is (1-5):1, and the ratio of MWCNTs to the mixed acid is (150-250) g: (35-45) mL; (2) Preparation of PTrp / MWCNTs / GCE polymer film modified electrode: polish the surface of the glassy carbon electrode, clean it with ultrasound and then air dry it; place the acidified MWCNTs in an anhydrous ethanol solution and ultrasonically disperse them to obtain a MWCNTs dispersion with a MWCNTs concentration of 0.5-2.0 mg / mL; drop the MWCNTs dispersion on the surface of the glassy carbon electrode and dry it to obtain MWCNTs / GCE; then place the MWCNTs / GCE electrode in a phosphate buffer solution containing 0.03-0.09 mol / L L-Trp, and scan 20-25 cycles in the range of -0.2-2.0 V by cyclic voltammetry to obtain a PTrp / MWCNTs / GCE polymer film modified electrode; (3) A three-electrode system was formed using a PTrp / MWCNTs / GCE polymer film modified electrode as the working electrode, a silver / silver chloride electrode as the reference electrode, and a platinum wire electrode as the counter electrode. Cyclic voltammetry and electrochemical impedance spectroscopy were then used to investigate the electrochemical behavior of L-glutamic acid on different modified electrodes. Differential pulse voltammetry was used to test L-glutamic acid at different concentrations, and a working standard curve was drawn. The standard addition method was then used to detect L-glutamic acid in the test samples.
2. The method according to claim 1, characterized in that In step (2), the surface of the glassy carbon electrode is polished using 0.3 μm and 0.05 μm alumina powders, respectively.
3. The method according to claim 1, characterized in that The diameter of the glassy carbon electrode in step (2) is 3 mm. 3.0-7.0 μL of MWCNTs dispersion is dropwise coated on the surface of the glassy carbon electrode and dried to obtain MWCNTs / GCE. The MWCNTs / GCE electrode is placed in 10.0 mL of phosphate buffer solution containing 0.03-0.09 mol / L L-Trp.
4. The method according to claim 1, characterized in that In step (3), the reaction was carried out at 2.0 mmol / L [Fe(CN)] 4- / 3- The electrochemical behavior of L-glutamic acid on different modified electrodes was investigated by cyclic voltammetry and electrochemical impedance spectroscopy in 0.20 mol / L Na2SO4 solution. Differential pulse voltammetry is used to test L-glutamic acid of different concentrations in an acetic acid-sodium acetate buffer solution, a working standard curve is drawn, and then the L-glutamic acid in the sample to be tested is detected by a standard addition method; the concentration of the acetic acid-sodium acetate buffer solution is 0.01-0.20 mol / L, and the pH of the acetic acid-sodium acetate buffer solution is pH 3.60-4.
20.
5. A L-glutamic acid detection sensor based on a polymer film modified electrode, characterized in that: The sensor comprises a polymer film modified electrode as a working electrode; the polymer film modified electrode comprises a glassy carbon matrix (5), the surface of the glassy carbon matrix (5) is modified with an acidified MWCNTs layer (6), the acidified MWCNTs layer (6) is loaded with a PTrp film layer (7), and the PTrp film layer (7) contains an L-Trp unit (9).
6. The sensor according to claim 5, characterized in that The sensor comprises a glassy carbon matrix (5) having a thickness of 1.0 to 5.0 mm, an acidified MWCNTs layer (6) having a thickness of 20 to 200 nm, and a PTrp film layer (7) having a thickness of 5 to 50 nm.
7. The sensor according to claim 5 or 6, characterized in that The sensor has a good linear relationship with the concentration of L-glutamic acid, and the linear range of detection is 5.000×10 -8 ~1.500×10 -5 mol / L, the detection limit is 2.580×10 - 8 mol / L.
Citation Information
Patent Citations
L-glutamic acid detection sensor based on polymer film modified electrode
CN210376223U